Pelatihan Menulis Cerita Pendek Untuk Komunitas Gemar Menulis Desa Bandul Kecamatan Tasik Putri Puyu Kabupaten Kepulauan Meranti - Muhammad Kafrawi; Evizariza Evizariza (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2021)
The community becomes a force to gather the younger generation to do positive things. One of the emerging communities is the literary community. In addition to conducting discussions on literary developments, the literary community also carries out writing training. This is what the Love Writing Community, Bandul Village, Tasik Putri Puyu District, Meranti Islands Regency, did. The main obstacle faced by the Love Writing Community is the lack of tutors or trainers for literary writing activities such as writing short stories. From this service, it can help members of the Bandul Village Love Writing Community understand writing strategies and at the same time the strategy of sending works to mass media that have cultural rubrics.